Tantrāyāna in Nusantara: Historical development of Tantra from Sriwijaya to the Gelgel Kingdom - Gede Agus Siswadi; Lasiyo; Rr. Siti Murtiningsih (Dharmakirti : International Journal of Religion, Mind and Science, 2026)
Background: This article examines the early emergence of Tantra and the historical development of Tantrāyāna in the Indonesian archipelago (Nusantara) by tracing the dynamics of transmission, transformation, and localization from South Asia to Southeast Asia. The discussion begins with a mapping of academic debates on the origins of Tantra, particularly between perspectives that emphasize the continuity of pre-Tantric practices and those that assert a sectarian origin of Tantra within Śaiva and Buddhist traditions. Method: This study employs a qualitative method with a historical–interpretative approach to investigate the development of Tantrāyāna in Nusantara from the early period to classical Balinese history. The research data are derived from library research, including primary texts, inscriptions, and relevant secondary scholarly works. Findings: The study demonstrates that Tantrism did not emerge as a static system, but rather developed as a fluid, dynamic, and cross-traditional historical process. In the South Asian context, the article highlights the interaction of Tantrism with Vedānta and Bhakti, as well as the diversity of philosophical interpretations, especially concerning non-dualism. The existence of esoteric Buddhist centers such as Sriwijaya, along with the development of Buddhist Tantra and Śaiva–Buddhist traditions in Java, indicates that Nusantara constituted a significant region in the history of Tantrāyāna. Through an analysis of Tantric texts, inscriptions, religious monuments, and Javanese–Balinese literary traditions, this article reveals the continuity of Tantric teachings from the Śailendra, Medang, Singasari, to the Majapahit periods. The discussion culminates in Bali as a distinctive space of Tantric localization, particularly through the transmission of Tantric teachings from East Java and Majapahit to the period of the Gelgel Kingdom of Bali. The roles of religious figures such as Dang Hyang Nirarta and Dang Hyang Astapaka are examined as central to the formation of Śaiva–Buddhist Tantric syncretism that underlies Balinese Hinduism. Conclusion: This article concludes that Tantrāyāna in Nusantara cannot be understood as a passive adoption from India, but rather as a religious tradition shaped through a creative, dialogical, and continuous process involving spiritual experience, political power, and local cosmology. Novelty/Originality of this article: This study finds that the Śaiva–Buddhist tradition that developed in Nusantara is deeply intertwined with Tantric teachings, and that the material and cultural remains of Hindu–Buddhist kingdoms in the Indonesian archipelago are closely connected to the influence of Tantrism.